2014
DOI: 10.2979/reseafrilite.45.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Style, Character, and the Theme of Struggle and Change: Chinua Achebe's <em>Anthills of the Savannah</em>

Abstract: Following insights from stylistic studies on European and American literature, as well as few earlier attempts on African literature, there has been a recent growing interest in the stylistic analysis of the African novel. The present study is meant to contribute to this growing literature by exploring Achebe's Anthills of the Savannah, primarily from a systemic functional linguistics perspective. Critics of the novel have emphasized that it represents Achebe's most articulate ideology on the sociopolitical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 8 publications
0
17
1
1
Order By: Relevance
“…Gaya bahasa merupakan bagian dari pilihan kata atau diksi (diction) yang mempersoalkan cocoktidaknya pemakaian kata, frasa atau klausa tertentu, untuk menghadapi situasi-situasi tertentu (Mwinlaaru, 2014). Gaya bahasa bersifat pribadi, dengan mempelajari gaya bahasa dari seorang pengarang atau sastrawan, akan dapat mengetahui dan menilai pribadi, watak, dan kemampuan dari si pengarang tersebut.…”
Section: Pendahuluanunclassified
“…Gaya bahasa merupakan bagian dari pilihan kata atau diksi (diction) yang mempersoalkan cocoktidaknya pemakaian kata, frasa atau klausa tertentu, untuk menghadapi situasi-situasi tertentu (Mwinlaaru, 2014). Gaya bahasa bersifat pribadi, dengan mempelajari gaya bahasa dari seorang pengarang atau sastrawan, akan dapat mengetahui dan menilai pribadi, watak, dan kemampuan dari si pengarang tersebut.…”
Section: Pendahuluanunclassified
“…Their story has unraveled the code, as Abdoulaye (2014) puts it: they are ensuring that "the anthills surviving to tell the grass (Beatrice, Elewa, et c) of the savannah about last year"s brush fires" (AOS: 31) do not miss details of the nation"s past horrors implied in the fires of, for example, genocide since the 1960"s. The Chief says "Nkolika" (Recalling-Is-Greatest) is a great name given a child as an affirmation and justification of something important to remember. To us listening to the Chief"s story and the Hymn, it is the struggle for true nationalism as implied also in Abdoulaye: 2014;Mwinlaaru: 2014;Gogoi: 2015. This is in answer to Chief"s question personifying the story: "Why do I say that the story is chief among his fellows?" Ikem and Chief have partly answered it: because the new generation is being taught how to "see" the proper way to the struggle, to "see" in a special way, to "see" what they have never known before (Marla Solomon: 1990).…”
Section: D) the Story Of Perennial Deprivation Among The Massesmentioning
confidence: 99%
“…On transitivity analysis of literary texts, several studies have made insightful contributions to African literature (Boukari & Koussouhon, 2018;Ezzina, 2015;Mwinlaaru, 2012Mwinlaaru, , 2014Somone, 2017). The much research in transitivity by Mwinlaaru (2012Mwinlaaru ( , 2014 has added to the repository of investigating African literature.…”
Section: Introductionmentioning
confidence: 99%
“…On transitivity analysis of literary texts, several studies have made insightful contributions to African literature (Boukari & Koussouhon, 2018;Ezzina, 2015;Mwinlaaru, 2012Mwinlaaru, , 2014Somone, 2017). The much research in transitivity by Mwinlaaru (2012Mwinlaaru ( , 2014 has added to the repository of investigating African literature. In 2012, he applied transitivity analysis to the narrative style of Ngugi's Weep Not Child, from which he reported that the transitivity patterns inscribe some functions to determine the psychological perspective the narrator relates to the story.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation